2022
DOI: 10.4102/phcfm.v14i1.3307
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety attitude among healthcare workers at different levels of healthcare in Sharqia Governorate, Egypt

Abstract: Background: Patient safety (PS) has been identified as a significant healthcare challenge. A good safety attitude helps healthcare workers (HCWs) to decrease medical errors.Aim: This study aimed to assess the PS attitude and identify its determinants among HCWs.Setting: This study was conducted in Sharqia Governorate at different levels of health care.Methods: This was a comparative cross-sectional study that involved240 HCWs selected after using a multistage cluster sampling technique from Sharqia Governorate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 26 publications
(30 reference statements)
1
9
1
Order By: Relevance
“…Additionally, Teleş & Kaya (40) found that the participants had 6 years of professional experience and worked for 60hrs or more per week, this indicates the shortage of nurses as a global and or may be increased demands of nurses services as a response to increasing populations and number of hospitals. The current result clarified that less than half of the studied nurses didn't receive training courses regarding patient safety, the result was similar to the research of Hussein, et al (13) entitled" Patient safety attitude among healthcare workers at different levels of healthcare in Sharqia Governorate, Egypt, reported that approximately fifth have prior training. This result indicates the need for continuously establishing more training programs on patient safety issues for all healthcare workers at all healthcare organizations.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Additionally, Teleş & Kaya (40) found that the participants had 6 years of professional experience and worked for 60hrs or more per week, this indicates the shortage of nurses as a global and or may be increased demands of nurses services as a response to increasing populations and number of hospitals. The current result clarified that less than half of the studied nurses didn't receive training courses regarding patient safety, the result was similar to the research of Hussein, et al (13) entitled" Patient safety attitude among healthcare workers at different levels of healthcare in Sharqia Governorate, Egypt, reported that approximately fifth have prior training. This result indicates the need for continuously establishing more training programs on patient safety issues for all healthcare workers at all healthcare organizations.…”
Section: Discussionsupporting
confidence: 87%
“…This result conflicts with Teleş & Kaya (40), , who found that almost half of the participants assigned a patient safety grade of acceptable. Additionally, this contrasted with Hussein, et al (13) who revealed that none of the participants rated the working unit as -excellent‖ in patient safety while more than half of them perceived it as acceptable, and a third rated it as very good. Moreover, Ali, et al (42) found that many of the surveyed participants perceived that their working unit had an acceptable patient safety grade.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Moreover, Tukey's Honest Significant Difference test was run to identify which group means are significantly different from another group's means. Tables 4,5 show the multiple comparison analysis of the variable of age and education level. As the Tukey post-hoc test shows in Table 4, the 31-40 years age group showed statistically different awareness levels as compared to the "more than 50 years age group" (p = 0.012).…”
Section: Components Of Patient Safety Awareness Culture (Psac)mentioning
confidence: 99%
“…Alnasser et al observe that the costs due to medication errors are approximately 42 billion USD per year ( 4 ). In Saudi Arabia, specifically, a research study by Eldeeb et al reveals that many healthcare practitioners, including nurses, have reduced levels of patient safety ( 5 ). Similarly, Khalil and his colleagues observe that the most serious events within the Saudi Arabia healthcare industry are related to allergic reactions due to medication errors ( 6 ).…”
Section: Introductionmentioning
confidence: 99%